(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
The article describes the role and importance of information technologies in the process of organizing distance education and independent education of geography under the conditions of the credit module system, the principles of using information and communication technologies and distance learning opportunities in the process of geography education.